Botulinum toxin A is an effective therapeutic tool for the management of parotid sialocele and fistula: A systematic review - Maharaj, Shivesh (Laryngoscope Investig Otolaryngol, 2020)
OBJECTIVES: In the management of parotid sialocele and fistula, various conservative and surgical methods have been described. Some studies have described the use of Botulinum toxin A (Botox A) for the management of parotid sialocele and fistula. This is a less invasive and potentially equally effective option. We therefore conducted a systematic review on the current body of literature relating to this specific use of Botox A. METHODS: A search strategy was conducted in July 2019 using the following electronic databases: Cochrane Database of Systematic Reviews, EMBASE, Google Scholar, PubMed, Scopus, and Web of Science. A search of all articles from inception until 31 August 2019 was performed. RESULTS: Literature searches of electronic databases identified 67 articles eligible for review, of which 15 fulfilled all criteria. These studies were small and in total only 47 patients were included. The majority of sialoceles and fistulas presented as a complication of surgery (77%) with the remaining cases occurring as a result of trauma. The typical age at presentation was between 32 and 88 years of age (mean age of 52 years). All patients were initially treated with and failed other conservative measures. Botox A injection was considered as a final conservative treatment option. The toxin was administered percutaneously in all cases of parotid sialocele and fistula. Dosage of Botox ranged from 10 to 200 units with majority of patients (58%) requiring only one injection. The overall success rate for patients treated with Botox A injections ranged between 70 and 100% for parotid sialoceles and fistulas. CONCLUSION: Botox A injections are successful in the treatment of parotid sialoceles and fistulas and should be considered before the use of invasive conventional options. Further studies with larger numbers are needed to ratify this recommendation. Success rate for patients, treated with Botox A injection was between 70 and 100% for parotid sialocele and fistula. Patients who failed initial treatment with Botox A were re‐administered with Botox A and eventually resolved.